Recent Advances in Natural Computing Selected Results from the IWNC 8 Symposium - Suzuki, Yasuhiro; Hagiya, Masami; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book highlights recent advances in natural computing, including biology and its theory, bio-inspired computing, computational aesthetics, computational models and theories, computing with natural media, philosophy of natural computing, and educational technology. It presents extended versions of the best papers selected from the "8th International Workshop on Natural Computing" (IWNC8), a symposium held in Hiroshima, Japan, in 2014. The target audience is not limited to researchers working in natural computing but also includes those active in biological engineering, fine/media art design, aesthetics, and philosophy.
Self-Organized 3D-Printing Patterns Simulated by Cellular Automata -- Cellular Automata Automatically Constructed from a Bioconvection Pattern -- A Comparison of Grouping Behaviors on Rule-Based and Learning-Based Multi-agent Systems -- Measurements of Negative Joint Probabilities in Optical Quantum System -- Brownian Motion Applied to Macroscopic Group Robots Without Mutual Communication -- Comparison of Tactile Score with Some Prescriptions in Artworks: From the Point of Media Transformation -- Drawing as the Relative Movement Between Subject and Medium: Using a Robot to Show the Subjectivity in Dynamic Flows of Consciousness -- Evolution of Honest Signal and Cry Wolf Signal in an Ecological system.
Keywords: Computational intelligence; Computer simulation; Mathematics -- Data processing; Mathematical statistics -- Data processing; Bioinformatics; Computational Intelligence; Computer Modelling; Computational Science and Engineering; Statistics and Computing; Computational and Systems Biology